(untitled) (Journal of Universal Science Research, 2025)
Reactive Arthritis (ReA) is an immune-mediated form of spondyloarthritis, often triggered by genitourinary or gastrointestinal infections. Current therapeutic strategies rely mainly on NSAIDs and cs-DMARDs, with biologics reserved for refractory disease. However, limited progress has been made in exploring novel targeted agents. Iguratimod 25 mg, an oral immunomodulatory drug approved for rheumatoid arthritis in Asia, has demonstrated anti-inflammatory and cytokine-suppressive properties, but evidence in ReA is scarce